Investigation on the laser transmission weldability and mechanism of the graft-modified polyethylene and PA66. Issue 1 (September 2016) - Liu, Huixia; Jiang, Hairong; Chen, Guochun; Guo, Dehui; Yan, Zhang; Li, Pin; Wang, Xiao
Abstract Because of great polar differences and poor compatibility, polyethylene (PE) and polyamide 66 (PA66) cannot be welded by laser transmission welding (LTW), even though they are widely used in our daily life. In this paper, using grafting modification technology to improve the welding performance between PE and PA66 is researched. First of all, two ways of the graft modified polyethylene (TGMPE) that the strong polar and reactive maleic anhydride (MAH) and glycidyl methacrylate (GMA) are grafted to PE respectively are introduced. Also, the mechanical and thermal performances of TGMPE are tested which show that the grafting modification has small influence on them. After TGMPE and PA66 are welded by laser, the high welding strength is found and the mechanism of the weldability between them is researched, which reveals that two reasons account for the high welding strength. For one thing, by observing the welding region micro morphology, it is not difficult to find that the grafting modification makes low interfacial tension, good compatibility, and strong interfacial adhesion between PE and PA66. At the same time, the good compatibility makes them easy to diffuse mutually, which causes some locking structures formed in the welding region. For another, the X-ray photoelectron spectrometer proves that chemical reactions are involved between TGMPE and PA66, which make the welding performance better. Afterward, the tensile failure forms of the welding are researched. At last, the welding strength of the MAH modified polyethylene and PA66 is compared to the GMA modified polyethylene and PA66.